EFFECTIVENESS OF THE SERVICE CERTIFICATION FOR LAND (Larasita) IN WEST LOMBOK - Jose Julian Syahral Haji (Jurnal IUS Kajian Hukum dan Keadilan, 2016)
This study, namely : To Analyze the effectiveness of the People’s Service land certification (Larasita) in West Lombok regency, and To Analyze any constraints that may affect the effectiveness of the People for Land Certification Service (Larasita) in West Lombok regency. In conducting this study, the authors use empirical research methods, namely: Empirical Research which is one type of legal research that analyzes and examines the workings of society Based on the survey results revealed that: 1. In the implementation of the program Larasita in West Lombok district is not operating effectively, this happens because of a lack of competent human resources, dissemination to the public related to the Larasita the program as well as the means and facilities for pre inadequate. 2. In the implementation Larasita program has many constraints, among others: a. Limitations on rural communication network, b. The scarcity administer, c. Unavailability of information and communication technology devices on cars Larasita, and d. lack of public awareness of the program Larasita.Keywords: Effectiveness and Larasita